Utilization of aerial sensor platforms for characterization of land-based, distributed radiological sources for radiological event response - Simerl, Nathanael (Kansas State University, 2022)
A method to characterize distributed radiological sources and the environment using an unmanned aerial vehicle (UAV) and commercial-of-the-shelf hardware and software was developed and implemented. High-altitude aerial surveys typically used for widespread distributed sources lack the spatial resolution needed to accurately describe the activity and exposure distributions at or near the ground. At this time, ground-truth measurements are necessary to normalize data collected at high altitudes, an operation that may not be feasible in certain scenarios. Furthermore, available prediction and modeling algorithms require multiple inputs which are unlikely to be available at the time of radiological release, resulting in an inadequate prediction of the spread of contamination. Low-level surveys circumvent these problems by directly measuring the exposure rate at the human level (1 m above the ground), eliminating the need for ground-truth normalization and the reliance on modeling and prediction algorithms. This research has shown that, when equipped with sufficient radiation detection systems, automated, low-level aerial surveys produce exposure rate maps that generally agree with ground-truth results and maintain a spatial resolution on the order of a few meters. The use of remote survey equipment reduces the radiological risk for response personnel, allowing for characterization of a site without direct exposure during the measurement process. UAVs may be used for measurements over distributed sources of various sizes, from a small radiological release via a radiological dispersal device, to a large-scale disaster (e.g., Fukushima Daiichi); the latter through the use of UAV swarms. These systems would also prove useful for localization of point sources. The research described herein includes the successful development and characterization of a ground-truth radiation detection system that uses a vehicle-mobile, collimated scintillator for activity distribution determination following three detonations of activated potassium bromide. A UAV-mounted scintillator system was characterized and implemented for aerial spectroscopic measurements over the same distribution to compare with the data from ground-truth measurements. UAV photogrammetry surveys were executed to form overhead maps and three-dimensional (3D) models of the test site. These maps and models were used to display radiological data from a standard overhead perspective, as a stand-alone 3D model, and in an explorable virtual environment. These methods comprise a complete radiological survey package that can mostly be implemented with easily-replaceable materials and at a relatively low cost, improving package flexibility and availability over specialized systems that rely heavily on custom hardware and software. This aspect is important as environmental conditions may increase the risk of losing the platform and payload due to a crash.
Keywords: Environmental monitoring; Radiation detector; Surface contamination; Surveys